2023
DOI: 10.1001/jamaneurol.2023.1184
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Autologous Hematopoietic Stem Cell Transplant vs Fingolimod, Natalizumab, and Ocrelizumab in Highly Active Relapsing-Remitting Multiple Sclerosis

Abstract: ImportanceAutologous hematopoietic stem cell transplant (AHSCT) is available for treatment of highly active multiple sclerosis (MS).ObjectiveTo compare the effectiveness of AHSCT vs fingolimod, natalizumab, and ocrelizumab in relapsing-remitting MS by emulating pairwise trials.Design, Setting, and ParticipantsThis comparative treatment effectiveness study included 6 specialist MS centers with AHSCT programs and international MSBase registry between 2006 and 2021. The study included patients with relapsing-remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…In this respect, indirect comparisons suggest that AHSCT may induce rates of NEDA remarkably higher than DMTs [ 2 , 29 ]. Even if head-to-head comparisons with HE-DMTs are lacking, possible superior effectiveness of AHSCT was suggested over natalizumab [ 2 , 30 ], fingolimod [ 30 ], and alemtuzumab [ 31 ]. Indeed, disease burden and accumulated disability are usually higher in the published experiences on AHSCT than in patients included in Registration Studies, therefore providing an unfavourable outcome scenario in AHSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, indirect comparisons suggest that AHSCT may induce rates of NEDA remarkably higher than DMTs [ 2 , 29 ]. Even if head-to-head comparisons with HE-DMTs are lacking, possible superior effectiveness of AHSCT was suggested over natalizumab [ 2 , 30 ], fingolimod [ 30 ], and alemtuzumab [ 31 ]. Indeed, disease burden and accumulated disability are usually higher in the published experiences on AHSCT than in patients included in Registration Studies, therefore providing an unfavourable outcome scenario in AHSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, AHSCT may represent an optimal front-loading strategy of costs in RR-MS, especially in cases bearing poor prognostic factors. Besides lower treatment-cost to prevent long-term disability accrual (almost half of the mean cost for HE-DMTs), AHSCT could offer further advantages as it may induce higher rates of disability improvement compared to HE-DMTs [ 30 ]. The latter effect may contribute to additional savings of the indirect costs related to loss of working abilities and social care expenditure: compared to mild disability, total costs for moderate and severe disability were recently estimated as 1.4–2.3-fold and 1.8–2.9-fold higher, respectively [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The comparative effectiveness of AHSCT vs. fingolimod, natalizumab and ocrelizumab in RRMS was explored in 167 AHSCT-treated patients who were propensity score matched to controls exposed to one of these DMTs, selected from the MSBase Registry [ 37 ]. Over 5 years, AHSCT was associated with a lower risk of relapses and a higher chance of disability improvement compared with fingolimod and natalizumab, with a similar effect on disability worsening.…”
Section: Efficacymentioning
confidence: 99%
“…Kalincik et al recently conducted a multicenter observational comparative study evaluating the efficacy of HSCT in comparison to other DMTs [ 12 ]. The study has demonstrated the superiority of HSCT over fingolimod in blunting relapse rates.…”
Section: Reviewmentioning
confidence: 99%